Design of Manually Reconfigurable Modular Manipulator with Three Revolute Joints and Links - Hong, Seonghun; Choi, Dongeun; Kang, Sungchul; Lee, Hyeongcheol; Lee, Woosub (2016 IEEE INTERNATIONAL CONFERENCE ON ROBOTICS AND AUTOMATION (ICRA), 2016)
Anthropomorphic arm manipulators usually consist of as a series of revolute joints and links. In this paper, serial-chain manipulators are described by a novel kinematic representation using a series of type R or T joints, which are classified according to relation between a rotational axis and two adjacent links. It provides an easy intuition to describe general types among existing manipulators and also to get intuitive ideas before designing of joint and link modules of modular manipulators. From these intuitive idea about joint configurations using two types of joints, a new concept of joint module with two input and one output connections is presented. This joint module enables to couple directly between two joint modules. In addition, practical solutions of mechanical and electrical connections between joint or link modules is introduced. The connection can be established between two modules via eight types of relative positions of 45 degree intervals. Using joint and link modules, 3-DoF(Degrees-of-Freedom) modular manipulators of three kinds of joint configurations are shown representatively. After assembly, the standard D-H(Denavit-Hartenberg) parameters of three examples are obtained utilizing information of joint and link modules.